Gazapos del lenguaje arquitectónico contemporáneo colombiano (REVISTA NODO, 2007)
Without the distinguishing magnificence of projects built in other parts of the world ever since the rise of postmodernism, there has been a subtle change of the architectural language in most of Colombia’s biggest cities over the same period oftime, one that resists any classification whatsoever, regardless of their resemblance with certain international tendencies, mainly because the architects lack the theoretical discourse envisioned by the authors of the original models. As a result, the article aims towards a meditation about the role of theory during the design conception; both as primary source to elaborate an architectural critic, and as a reliable instrument to pass judgment on the aesthetic contribution of buildings up to now mistakenly called unidentified flying objects.
Keywords: Architectural language; postmodernism; theory; identity; Colombian architecture